Failure Behavior and Energy Storage and Release of Hard Coal under Different Static and Dynamic Loading States - XianJie Hao; GuangYao Pan; Chaoxing Ma; Yingnan Wei; Zeyu Chen (Advances in Civil Engineering)
The study of the energy accumulation and rate of release in hard coal under dynamic, static, and coupled dynamic-static loading and its failure mode is of significance when studying the mechanism underpinning coal mine dynamic disasters such as rock burst, coal, and gas outburst. In this paper, four experimental methods (uniaxial compression, Brazilian splitting, and coupled dynamic-static tensile and coupled dynamic-static compression) were used to analyze the energy accumulation, energy rate of release, and failure modes of this type of hard coal under different loading conditions. It was concluded that (1) the energy accumulation and rate of releases of this type of hard coal under static compression are 17.63–179.90 times and 18.57–13157.89 times those under static tension; the energy accumulation and rate of releases in dynamic compression are 2.11–248.53 and 0.23–48 times those under dynamic tension, respectively. (2) During dynamic loading, the ratio of compressive energy accumulation to tensile energy accumulation is reduced by 1.6 times compared with static loading, and the ratio of compressive energy release to tensile energy rate of release is decreased by 363.84 times compared with static loading. (3) The energy accumulation and rate of releases of this type of hard coal for dynamic tensile are, respectively, 2.64–17.42 and 1.07–5.26 times those under static tensile load; the energy accumulation under dynamic compression is greater than that under static compression, being 0.24–15.04 times that under static compressive, but the energy rate of release under dynamic compression is 0.0003–0.56 times that under static compression. (4) The greater the prepeak energy accumulation, the greater the degree of damage of the coal sample at each stage, and also the higher the degree of fragmentation after the failure. The research results play an important guiding role in further understanding the mechanism of coal mine dynamic disasters.